2013
DOI: 10.1517/14740338.2013.797407
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular safety and hemodynamic considerations in oncology drug development – webinar highlights October 10th 2012

Abstract: Oncology drug-induced cardiotoxicity has recently been recognised as an important drug development and clinical issue. The recognition of the risks and opportunities has prompted intensive research into mechanisms of chemotherapy-induced cardiotoxicity and potential prevention strategies. Drug-induced blood pressure elevation has emerged as a key area of interest, both as a marker of efficacy of vascular targeted chemotherapies as well as a target for early intervention strategies. While further research is on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…It is highly likely that some of the patients in the CS group did take hormone replacement medication as part of their adjuvant therapy. Our results on blood pressure are similar to those recently reported by Braddock et al ( 2013) that have shown that both medication, including chemotherapy, and other adjuvant therapies (radiotherapy) had an effect on blood pressure (Braddock et al 2013). …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is highly likely that some of the patients in the CS group did take hormone replacement medication as part of their adjuvant therapy. Our results on blood pressure are similar to those recently reported by Braddock et al ( 2013) that have shown that both medication, including chemotherapy, and other adjuvant therapies (radiotherapy) had an effect on blood pressure (Braddock et al 2013). …”
Section: Discussionsupporting
confidence: 92%
“…Hormone therapy has been shown to elevate blood pressure in women (Braddock et al 2013). It is highly likely that some of the patients in the CS group did take hormone replacement medication as part of their adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is limited by a small sample size, which prevented stratification by breast cancer treatments and the control of length of time post-cancer treatment. As there is evidence that breast cancer treatments, including chemical variations in drugs used for chemotherapy, may have varying effects on metabolism [ 47 ], future studies should attempt to stratify by treatment. There is limited data available on the impact of duration of survivorship on the observed relationships; however, there is evidence that subjective outcomes (i.e.…”
Section: Discussionmentioning
confidence: 99%